Endoscopic Renal Cyst Ablation - Tadayon, Alireza; A’yanifard, M; Mansoori, Daryoosh (Urology Journal, 2009)
Purpose: To evaluate the result of simple renal cyst ablation by endoscope and compare the results with other techniques of renal cyst treatment. Materials and Methods: A prospective study was performed at Shaheed Faghihi hospital from January 2001 to January 2003. Ten patients with symptomatic simple renal cyst were selected for this study. The exclusion criteria were history of previous renal surgery, parapelvic cyst, and cyst size less than 50 mm. Urinalysis, urine culture, serum electrolytes, ultrasonography, and CT scan were done before operation. The patients underwent endoscopic renal cyst ablation and cytology of cyst fluid and histopathological examination of cysts’ walls were done in all patients. The patients were followed with ultrasonography after two weeks and 2, 6, and 12 months postoperatively. Disappearance of the cyst or decreasing its size to less than 50% of its primary size was considered as improvement. Results: All the patients were female with a mean age of 55 (range 22 to 75) years. The operation was successful in 9 patients with no major complications. Perinephric hematoma and excessive leakage were seen in two patients. The operative time was 38±10.8 minutes and hospital stay was 3±1.3 days. Mean size of cyst before operation was 75±19.7 mm and changed to 12.7±15.3 mm after operation (p Conclusions: Cyst ablation can be used for the treatment of simple renal cysts not responding to aspiration and sclerosing therapy, and if there is no laparoscopic facility. More studies are needed to confirm these results.